4-Hydroxytamoxifen is a potent inhibitor of the mitochondrial permeability transition - Cardoso, Carla M. P. (2002)
The effects of 4-hydroxytamoxifen (OHTAM), the major active metabolite of the antiestrogen tamoxifen used in the breast cancer therapy, were studied on the mitochondrial permeability transition (MPT) and bioenergetic functions of mitochondria to evaluate the mechanisms underlying the cell death and toxic effects. The MPT was induced in vitro by incubating rat liver mitochondria with 1 mM inorganic phosphate plus Ca2+ and with tert-butyl hydroperoxide. OHTAM provides protection against the Ca2+-induced mitochondrial swelling, depolarization of the mitochondrial membrane potential ([Delta][Psi]), loss of electrophoretic Ca2+ uptake capacity and uncoupling of respiration, similarly to cyclosporine A. The concentrations of OHTAM used do not significantly affect [Delta][Psi], respiratory control and adenosine diphosphate/oxygen ratios and induce repolarization and Ca2+ re-uptake, suggesting that such inhibitory effects of OHTAM were due to the prevention of the MPT induction and not due to the inhibition of the mitochondrial Ca2+ uniporter. Since the MPT induction has been linked to an oxidized shift in the mitochondrial redox state and/or increase in the generation of reactive oxygen species, the MPT prevention by OHTAM may be related to its high antioxidant capacity.